Genetic interpretation and clinical translation of minor genes related to Brugada syndrome. Issue 6 (29th March 2019) - Campuzano, Oscar; Sarquella‐Brugada, Georgia; Fernandez‐Falgueras, Anna; Cesar, Sergi; Coll, Monica; Mates, Jesus; Arbelo, Elena; Perez‐Serra, Alexandra; del Olmo, Bernat; Jordá, Paloma; Fiol, Victoria; Iglesias, Anna; et al.
Abstract: Brugada syndrome (BrS) is an inherited arrhythmogenic disease associated with sudden cardiac death. The main gene is SCN5A . Additional variants in 42 other genes have been reported as deleterious, although these variants have not yet received comprehensive pathogenic analysis. Our aim was to clarify the role of all currently reported variants in minor genes associated with BrS. We performed a comprehensive analysis according to the American College of Medical Genetics and Genomics guidelines of published clinical and basic data on all genes (other than SCN5A ) related to BrS. Our results identified 133 rare variants potentially associated with BrS. After applying current recommendations, only six variants (4.51%) show a conclusive pathogenic role. All definitively pathogenic variants were located in four genes encoding sodium channels or related proteins: SLMAP, SEMA3A, SCNN1A, and SCN2B . In total, 33.83% of variants in 19 additional genes were potentially pathogenic. Beyond SCN5A, we conclude definitive pathogenic variants associated with BrS in four minor genes. The current list of genes associated with BrS, therefore, should include SCN5A, SLMAP, SEMA3A, SCNN1A, and SCN2B . Comprehensive genetic interpretation and careful clinical translation should be done for all variants currently classified as potentially deleterious for BrS.